An Atypical Path of a Bullet in Thorax in a Firearm Injury Case Report - Çobanoğlu, Ufuk; Can, Muhammet (The Bulletin of Legal Medicine, 2008)
Various weapons have been used in the history of mankind for defence and attack. With the progression of new technologies numerous types and greater destroying effects accompanied these weapons. Bullets of gunshots can be localised in different regions from the entry point due to its high kinetic energy and tissue contact. Fourty eight years old male was admitted to emergency unit due to gun shot injury on the chest. Bullet entered thorax from 4. intercostal space. It passed through upper lobe by causing injure paranchyme and toward sternum. It entered to right hemithorax by pericardial laceration and rupture of internal mammary artery and then changed its direction downward. Following right lower lobe laseration and 7. rib fracture, it directed upward and left thorax from 5.intercostal space. It injured medial border of scapula and setteled down to posterior of scapula. This case was discussed for its interesting outcome due to an atipical route in the chest with a gunshot bullet.Key words: Gunshot bullet core, atipical route, chest cavity, forensic case
Keywords: gunshot bullet core; atipical route; chest cavity; forensic case